Spontaneous pneumomediastinum and pneumothorax in a non-intubated patient with coronavirus disease 2019 pneumonia: A case report - Angela Iuorio,; Giacomo Torretta,; Pierluigi Fusco,; Maurizio Ferrara, (Indian Journal of Case Reports, 2021)
Coronavirus disease 2019 (COVID-19) has rapidly spread across the globe. Many studies have shown its typical and atypical clinical presentations. Pneumothorax and pneumomediastinum have both been noted to complicate cases of COVID-19 requiring hospital admission even in the absence of mechanical ventilation. The major described pathophysiological mechanism is diffuse alveolar injury leading to alveolar rupture and air leak. Here, we describe a case of spontaneous pneumomediastinum and pneumothorax in a non-intubated patient after sixteen days of initial symptoms of COVID-19.